The Consolidated Medium-Term Income and Expenditure Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
The medium-term income projections have been updated since the last estimate provided to the Executive Board in April 2014. The main changes to the outlook stem from a lower path for credit outstanding and expectations for a more gradual rise in interest rates. The revised projections show lower levels of net operational income over the coming years. Lending income is lower compared with earlier estimates as a result of lower credit levels, including the advance repurchases by Ireland and Portugal. Non-lending income is also projected to be lower reflecting a further downward shift in SDR interest rates and, thus, returns on investments and interest-free resources. The updated expenditure path assumes the net administrative budget remains constant in real terms at the FY 2012 level. The long-run projections indicate a broad balance between income and expenditures, assuming that interest rates rise to 3.5 percent and with lending returning to pre-crisis levels. The pace of reserve accumulation is expected to slow, reflecting the decline in Fund credit, and precautionary balances are now projected to remain slightly below the projected target of SDR 20 billion over the medium term compared with the earlier estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet